Microstructural Changes in Patients With Parkinson's Disease Comorbid With REM Sleep Behaviour Disorder and Depressive Symptoms - Ghazi Sherbaf, Farzaneh; Rostam Abadi, Yasna; Mojtahed Zadeh, Mahtab; Ashraf-Ganjouei, Amir; Sanjari Moghaddam, Hossein; Aarabi, Mohammad Hadi (Frontiers in Neurology, 2018)
The diagnosis of Parkinson’s disease (PD) is currently anchored on clinical motor symptoms, which appear for more than 20 years after initiation of neurotoxicity. Extra-nigral involvement in the onset of PD with probable nonmotor manifestations before the development of motor signs, lead us to the preclinical (asymptomatic) or prodromal stage of the disease (various nonmotor or subtle motor signs). REM sleep behaviour disorder (RBD) and depression are established prodromal clinical markers of PD and predict worse motor and cognitive outcomes. Nevertheless, taken by themselves, these markers are not yet claimed to be practical in identifying high-risk individuals. Combining promising markers may be helpful in a reliable diagnosis of early PD. Therefore, we aimed to detect neural correlates of RBD and depression in 93 treatment-naïve and non-demented early PD by means of diffusion MRI connectometry. Comparing four groups of PD patients with or without comorbid RBD and/or depressive symptoms with each other and 31 healthy controls, we found that these two nonmotor symptoms are associated with lower connectivity in several white matter tracts including the cerebellar peduncles, corpus callosum and long association fibers (cingulum, fornix and inferior longitudinal fasciculus). For the first time we were able to detect the involvement of short association fibers (U-fibers) in PD neurodegenerative process. Longitudinal studies on larger sample groups are needed to further investigate the reported assciations.